Implikasi Penolakan Bukti Elektronik Tanpa Verifikasi Digital Forensik: Studi Putusan dan Analisis Yuridis - Tiba, Stefania Kandida Sena (Media Hukum Indonesia (MHI), 2026)
The rapid development of the digital era has significantly influenced judicial proceedings, particularly with regard to the use of electronic evidence. Nevertheless, not all electronic evidence is admissible in court, as reflected in Decision Number 488/Pid.B/2024/PN Sda. The rejection of the evidence was grounded in the absence of guaranteed authentication, despite the fact that authentication constitutes a fundamental aspect, given the decisive role of evidence in establishing the facts of a criminal case. Therefore, the application of digital forensic mechanisms is essential to verify the authenticity and reliability of electronic evidence so that it may be recognized as legally valid in court proceedings. Legal provisions concerning the admissibility of electronic evidence and the necessity of forensic verification have been accommodated in the Law on Information and Electronic Transactions (ITE Law), as amended, as well as in the Indonesian Criminal Procedure Code. This study aims to juridically examine the reasons underlying the rejection of electronic evidence in Decision Number 488/Pid.B/2024/PN Sda and to emphasize that the implementation of digital forensics on electronic evidence constitutes an absolute requirement for its acceptance as legally valid evidence in judicial proceedings.